Effect of Enhancement Material on the Performance of Ground Electrodes Under Impulse Conditions - Usman Muhammad; Nurul Nadia Ahmad; Normiza Mohamad Nor; Fazlul Aman (IEEE Access, 2025)
Among the factors that affect the soil resistivity is the chemical content in soil, where the ionic conduction is expectedly increased and the soil resistivity is reduced. Due to the beneficial use of chemical composition in soil, enhancement materials (EMs) or salts have been widely used in an effort to obtain a low ground resistance value. Much published data on the performance of the EMs on the steady-state resistance value is available; however, not much data is available on its characteristics under high impulse conditions by field measurements. In this paper, experimental test results on twelve configurations (six configurations with the EM and without the EM) installed in situ and tested under impulse conditions are reported. The study aims to quantify the effects of ground electrode configurations and EM on the soil characteristics under high impulse conditions, providing valuable insights for optimising grounding system design. Results show that the steady-state ground resistance is reduced by over 40% for most configurations with EM, significantly improving the current discharge time under impulse conditions. Additionally, inductive effects were more pronounced in configurations with lower resistance, particularly at higher voltages, while the impulse impedance was current-dependent for configurations without EM, whereas those with EM were less affected by current magnitude. CDEGS simulations indicated that parallel configurations are more prone to inductive effects than grid configurations, with electrode shape having a greater influence than size.